Harrod's Growth Model: An Illumination using the Multiplier-accelerator Model - Coleman, William (School of Management Working Papers, 1990)
It is shown that Multiplier-Accelerator models under plausible parameter assumptions manifest the two Harrod Propositions; a Unique Warranted Rate of growth and a Knife Edge.